2020
DOI: 10.1371/journal.pone.0234931
|View full text |Cite
|
Sign up to set email alerts
|

The attitude of kidney transplant recipients towards elective arteriovenous fistula ligation

Abstract: Background Arteriovenous fistulas (AVF) are a source of various complications. Among previously hemodialyzed kidney transplant recipients (KTxR), the AVF may persist over time. The patients' decisions whether to ligate the functioning AVF may be prompted by many factors. Our knowledge of benefits concerning the procedure as well as patients' attitude towards it is scarce. Aim Evaluation of the patients' opinion on the persistent AVF ligation after a successful kidney transplantation. Materials and methods An a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Finally, majority of the patients did not want to close the AVF. It is in line with our questionnairebased study (8). It could be a consequence of our former view that the cardiovascular effect of a functioning AVF is mild and high prevalence of distal AVFs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Finally, majority of the patients did not want to close the AVF. It is in line with our questionnairebased study (8). It could be a consequence of our former view that the cardiovascular effect of a functioning AVF is mild and high prevalence of distal AVFs.…”
Section: Discussionsupporting
confidence: 91%
“…The results of a recent meta-analysis demonstrated that AVF closure was related with an improved cardiac morphology, and a better kidney graft function and AVF closure had been suggested as a considerable approach in patients with a well-functioning allograft (32). Despite the modification of the cardiovascular risk through an intervention on AVF seems to be a promising intervention in KTx recipients, the patients were not convinced to a routine VA ligation (8). An alternative option could be a precision flow reduction by banding with a real-time access flow assessment or banding with the use of a sizing dowel (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38.5% of patients never wanted to ligate the AVF, and 38.5% of patients had no clear opinion. Paradoxically, patients with the worst kidney graft function and a distally located AVF had the highest proportion of individuals willing to ligate their vascular access [29].…”
Section: Discussionmentioning
confidence: 99%
“…The individual risk of graft dysfunction and a return to chronic HD needs to be balanced [32]. There is also a clear need to educate patients about posttransplant AVF management options [29].…”
Section: Discussionmentioning
confidence: 99%